Peran Layanan Program SAMSAT Keliling dalam Meningkatkan Pendapatan Daerah di SAMSAT Kabupaten Sukabumi - Ismet Ismatullah; Muhammad Raihan Maulana; Reni Anggraini (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
Mobile vehicle tax service is one of the regional government initiatives designed to facilitate tax compliance and increase regional revenue. This study aims to examine the contribution of mobile tax units in boosting local revenue in Sukabumi Regency. The methodology applied in this research is a descriptive qualitative approach, with data collection conducted through direct observation. The findings reveal that the implementation of mobile tax units produces significant effects on increasing the number of taxpayers, resulting in higher local revenue from the vehicle tax component. This service has also successfully reached remote areas previously difficult to access by conventional tax offices. Therefore, mobile tax units can be considered effective as a sustainable strategy to optimize regional income.